2017
DOI: 10.1111/resp.13180
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term respiratory effects of e‐cigarettes in healthy individuals and smokers with asthma

Abstract: A single session of ECS had respiratory mechanical and inflammatory effects, which were more prominent in smokers with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 24 publications
5
71
0
4
Order By: Relevance
“…Taken together, the data for this one study of e‐cigarette use found no convincing evidence of benefit but may indicate detrimental effects compared to current best practice. This is consistent with evidence that a single session of e‐cigarette use has immediate, adverse mechanical and inflammatory respiratory effects in patients with mild asthma …”
Section: Asthmasupporting
confidence: 89%
“…Taken together, the data for this one study of e‐cigarette use found no convincing evidence of benefit but may indicate detrimental effects compared to current best practice. This is consistent with evidence that a single session of e‐cigarette use has immediate, adverse mechanical and inflammatory respiratory effects in patients with mild asthma …”
Section: Asthmasupporting
confidence: 89%
“…The current review also highlighted the adverse effect of vaping on asthma, which similarly to that of smoking, is translated in asthma exacerbation with potentially more frequent, severe, or difficult to control asthma attacks [54,202].…”
Section: Respiratory Injuriesmentioning
confidence: 99%
“…The short‐term effects of e‐cigarette smoking were studied in a group of smokers with and without mild asthma . The key finding was that brief e‐cigarette exposure induced both central and peripheral airway obstruction in both groups, although the changes were more pronounced and of longer duration in those with asthma.…”
Section: Asthmamentioning
confidence: 99%